Evaluation of the COBAS AMPLICOR MTB system. - Bodmer, T (1997)
A panel of 1,012 respiratory sediments was retrospectively tested by PCR amplification to detect Mycobacterium tuberculosis with the COBAS AMPLICOR MTB system. The sensitivities and specificities of COBAS and fluorescence microscopy compared to culture were 92.6 versus 95.6% and 99.6 versus 95.3%, respectively. Inhibition occurred in 48 (4.7%) specimens.